No-tillage effects in bean cultivation and the application of fomesafen on soil dynamics - Martins, Heytor Lemos; Korasaki, Vanesca; Peixoto, Pedro Gomes; Martins, Eduardo da Silva; Benedito, Vitor Adriano; Campalle, Arthur Nardi; Barbosa, Gabriela de Sousa; Alves, Pedro Luís da Costa Aguiar (Australian journal of crop science, 2025)
Soil quality is defined as the measure of its capacity to perform vital ecological functions for agricultural development. With the expansion of cultivated areas and even their exposure to long periods without plant presence, issues such as erosion and soil nutrient depletion can arise. Therefore, practices like crop rotation or the incorporation of green manures have gained traction in soil preparation for large-scale cultivation. The common bean plant, being a member of the legume family, possesses such capabilities, being a potential nitrogen fixer and contributing to soil maintenance. Thus, this study aimed to assess the effects of cultivating common beans in fallow areas with sugarcane straw and fomesafen application. The experiment was conducted in an area with Eutrophic-Dystrophic Red Latosol. The experimental design was a randomized block design in a 4x2 factorial system, with four replicates, considering leaves straw presence (0, 1, 5, and 10 t ha-1) and two types of herbicide application (with and without application), totaling 8 experimental treatments and 32 plots. Soil chemistry, soil enzymatic activity, leaf area, plant dry matter, and productivity were evaluated. Higher straw quantities in the system improved soil enzymatic activity dynamics and soil chemistry. Plant development was correlated with higher soil enzymatic activity. Thus, it is concluded that in fallow areas: 1) the straw enhances soil quality and common bean productivity; 2) The herbicide (fomesafen) application has no impact on soil dynamics; 3) chemical, physical, and biological soil variables show worse conditions in treatments without straw, regardless of herbicide application; 4) enzymatic activity (β-glucosidase) is higher in the interaction between straw and plants, responding better to soil dynamics compared to physical and chemical variables, resulting in higher common bean productivity. It is recommended to maintain or increase straw coverage to improve soil quality and common bean productivity, with the safe use of the herbicide fomesafen, as it does not negatively affect soil dynamics.